Field and Transformation in Relation to Biological Form - Paton, Ray (Theoria et Historia Scientiarum, 2008)
Ideas about field and transformation are especially important in modem physics and have also made an impact of biological thinking in various ways. The purpose of this paper is to look at some integrative ideas in biology that access field and transformational thinking, particularly in relation to form. The paper begins with a brief consideration of some philosophical schools of thought that may and do influence thinking about form. This is followed by a consideration of relations between field and form in the work of Gurwitsch and Thompson. Finally, Thompson’s transformational approach to comparative forms is considered with regard to interactions between biological forms and their environments.